Fairy tales of Eastern Europe - Philip, Neil.; Wilkes, Larry (New York Clarion Books, 1991)
A collection of fairy tales from Eastern Europe and the Soviet Union, including "God's Cockerel" and "Cinder Jack."
Keywords: Fairy tales -- Europe, Eastern; Fairy tales -- Soviet Union; Fairy tales; Folklore -- Europe, Eastern; Folklore -- Soviet Union